Distribuição da floresta urbana e sua relação com índices socioeconômicos no município de Araras (SP) - Fonzar, Camila Santos (Universidade Federal de São Carlos, 2025)
The implementation of urban forests in Brazil was intensified from the 1930s, driven by public policies aimed at modernizing urban centers. However, medium and small Brazilian cities, in particular, still show an unequal distribution of this component, with tree cover concentrated in central and higher-income areas. In this context, this research aimed to evaluate the urban forest of the city of Araras (SP), relating the distribution of the tree component to socioeconomic indicators. The methodology employed a quantitative and spatial approach, analyzing urban census tracts using IBGE data and the UrbVerde platform to calculate accessibility, with the 3/30/300 rule as a background. The statistical analysis sought to correlate compliance with the rule’s components with average income and the proportion of children and elderly in each sector. The results indicate that the municipality’s performance regarding the rule is heterogeneous. The accessibility criterion, the “300” component, had the highest adherence, reaching 32% of the evaluated sectors. Next was the visibility criterion, with 13% adherence, and finally, the tree cover criterion, which had the lowest adherence rate at only 9%. The combined analysis showed that no census tract fully meets all three components. The analysis revealed a positive and significant correlation between income and tree cover, the “30” component, indicating that lower-income areas are less wooded. In contrast, no statistically significant correlations were observed between income and the other components of the rule. Demographic analyses indicated that sectors with a higher proportion of elderly residents had a lower perception of tree cover in their surroundings (component “3”), while sectors with a higher proportion of children tended to be farther from public green areas, revealing specific environmental vulnerabilities for each group. It is concluded that the 3/30/300 rule proved to be an effective diagnostic tool for identifying green infrastructure deficits and guiding urban public policies that promote socio-environmental justice and climate resilience in medium-sized cities.
Distribution of urban forest and its relationship with socioeconomic indicators in the municipality of Araras (SP)
Keywords: Geoprocessamento; Justiça-socioambiental; Urban forestry; Geoprocessing; Socio-environmental justice; Socio-environmental justice; CIENCIAS AGRARIAS::AGRONOMIA; 3. Saúde e Bem-Estar; 10. Redução das Desigualdades; 13. Ação contra a Mudança Global do Clima; 15. Vida Terrestre